Integrating Next-Generation Sequencing in the Clinical Pharmacogenomics Workflow - Giannopoulou, Efstathia; Katsila, Theodora; Mitropoulou, Christina; Tsermpini, Evangelia-Eirini; Patrinos, George P. (Frontiers in Pharmacology, 2019)
Pharmacogenomics has been recognized as a fundamental tool in the era of personalized medicine with up to 266 drug labels, approved by major regulatory bodies, currently containing pharmacogenomics information. Next-generation sequencing analysis assumes a critical role in personalized medicine, providing a comprehensive profile of an individual’s variome, particularly that of clinical relevance, comprising of pathogenic variants and pharmacogenomic biomarkers. Here, we propose a strategy to integrate next-generation sequencing into the current clinical pharmacogenomics workflow from deep resequencing to pharmacogenomics consultation, according to the existing guidelines and recommendations.